Tourism's destination dominance and marketing website usefulness - Woodside, Arch; Vicente, R.; Duque, M. (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this article is to propose and test empirically tourism's destination dominance and marketing website usefulness hypothesis (TDDH). The study proposes a multi-item metric for marketing website usefulness. The main hypothesis is that the usefulness of a destination's marketing website associates positively with the dominance of tourism in the destination. Design/methodology/approach – The following ratio defines tourism's destination dominance: the number of tourists visiting annually to a destination's residential population. The method includes creating a multi-item metric for judging the usefulness of a destination's marketing website. The study applies the metric in evaluating the usefulness of 40 destination marketing websites. Findings – The study's findings indicate a significant relationship between tourism destination dominance and marketing website usefulness. The effect size of this relationship is small. The small effect size indicates that some destinations with relatively few tourists (relative to the destination's residential population) do include substantial amounts of information in their websites and some destinations with relatively many tourists do not do so. Research limitations/implications – The usefulness of a destination's website for potential visitors does not relate substantially to tourism's dominance in the destination. Some destinations with relatively few tourists are highly competent in designing websites that are highly useful for potential visitors. Originality/value – Providing a discussion of alternative tourism destination dominance metrics, confirming the view that destination marketing websites vary in their usefulness for potential visitors and offering a metric for testing usefulness are the valuable contributions of the study.